SYNTHESIS, CHARACTERIZATION, DFT, AND BIOLOGICAL ASSAY OF NEW XANTHATE COMPLEXES WITH NITROGEN BASES : Synthesis, Characterization and DFT Study of 2-Phenoxyethyl Xanthate Ligand and Complexes with Transitions Metals and their Adducts with Nitrogen Base Ligands - Molla-Babaker, Mohammed M.; Khalid, Maher; AL-Mukhtar, Saad.E. (Science Journal of University of Zakho, 2024)
This study introduces a new series of complexes and adducts, denoted by [M(2-PhOEtXant)2.nL], where M represents Mn(II), Fe(II), Co(II), or Ni(II), and the ligand (2-PhOEtXant) is 2-Phenoxyethylxanthate. Varying ligands, including pyridine, piperidine, quinoline, ethylenediamine, and (1,10)-phenanthroline, are explored based on the value of n. Comprehensive characterization, encompassing techniques like 1H-NMR, 13C-NMR, FTIR, AA, CHN analysis, UV-visible spectroscopy, and magnetic property measurements, is employed. Results indicate an octahedral geometry for these complexes, as revealed by effective magnetic moment measurements and electronic spectra analysis. The compounds exhibit noteworthy antioxidant properties, demonstrated through the DPPH radical scavenging method, highlighting their potential as effective antioxidants. Moreover, the complexes display enhanced antibacterial activity against microbial strains compared to free ligands. This research not only delves into the coordination chemistry of these complexes but also underscores their diverse applications. Combining experimental methods with computational insights using Density Functional Theory (DFT) enhances the understanding of dithiolate transition metal complexes. The alignment of computational and experimental outcomes strengthens the reliability of the findings, laying a robust foundation for interdisciplinary exploration. The identified potential applications in optoelectronics, along with the notable antioxidant and antibacterial activities, position these complexes as promising contenders for advanced technologies and scientific applications.
Keywords: Complexes of [Manganese (ll); Iron (ll); Cobalt (ll) & Nickel (ll); Xanthate Salt; Hexa-coordinate complexes and Xanthate complexes.